2013
DOI: 10.1177/1059712313491612
|View full text |Cite
|
Sign up to set email alerts
|

Social contracts and human–computer interaction with simulated adapting agents

Abstract: Game theory is commonly used to study social behavior in cooperative or competitive situations. One socioeconomic game, Stag Hunt, involves the trade-off between social and individual benefit by offering the option to hunt a low-payoff hare alone or a high-payoff stag cooperatively. Stag Hunt encourages the creation of social contracts as a result of the payoff matrix, which favors cooperation. By playing Stag Hunt with set-strategy computer agents, the social component is degraded because of the inability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 37 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…The authors would like to add a note of caution regarding interpretation of the results of this study as being characteristic of human–human interaction during these particular games. Others have noted differences in behavioral outcomes between humans playing in pairs with one another and humans playing with deterministic strategies (Harford and Solomon, 1967 ; Craig et al, 2013 ). Had the participants played in pairs with each other we would expect more variability in outcomes during the games and in the responses to the state trust questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors would like to add a note of caution regarding interpretation of the results of this study as being characteristic of human–human interaction during these particular games. Others have noted differences in behavioral outcomes between humans playing in pairs with one another and humans playing with deterministic strategies (Harford and Solomon, 1967 ; Craig et al, 2013 ). Had the participants played in pairs with each other we would expect more variability in outcomes during the games and in the responses to the state trust questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Human participants who played PD and CG with other human participants exhibited deep transfer of learning effects (Juvina et al, 2013 ), whereas these effects were absent when participants played the same games with a scripted agent, as shown above. Craig et al ( 2013 ) have suggested that, although having participants play games with simple predetermined strategies (e.g., T4T and Pavlov) allows for more experimental control during games of strategic interaction, these strategies may give rise to less interesting behavioral effects. We suggest that future research should examine the behavior of individuals when playing games of strategic interaction with more complex models, such as the one presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Game-based digital interventions have been found to have practical effects in addressing the main barriers of access and engagement in the healthcare domain, particularly for the young. 6 Evidence from neuropsychological research further suggests the therapeutic value of game-based digital interventions in depression therapy, finding that positive game-playing experiences trigger the release of hormones such as endorphins and striatal dopamine 7,8 that are responsible for feelings of pleasure and well-being. 9,10 Guided by reasoning, game-based interventions have specific potential for reducing depression through the natural benefits afforded by the game elements involved.…”
Section: Introductionmentioning
confidence: 98%
“…This allows for more organic player behavior that resembles interactions with a human subject. The advantage of using an adaptive agent over human subjects is that experimenters have greater control over how the agent performs, addressing a weakness commonly found in the highly variable and complex decision-making strategies of humans ( Craig et al, 2013 ). Furthermore, adaptive agents themselves are a source of information, as it is possible to examine their internal processes and strategies that develop in response to the game environment.…”
Section: A Multidisciplinary Paradigm To Investigate the Serotonergicmentioning
confidence: 99%